2011
DOI: 10.1152/jn.00469.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Motor Cortical Neurons Contributes to Intralimb Coordination During Reaching in the Cat by Modulating Muscle Synergies

Abstract: We examined the contribution of the motor cortex to the control of intralimb coordination during reaching in the standing cat. We recorded the activity of 151 pyramidal tract neurons (PTNs) in the forelimb representation of three cats during a task in which the cat reached forward from a standing position to press a lever. We simultaneously recorded the activity of muscles in the contralateral forelimb acting around each of the major joints. Cell activity was recorded with and without the presence of an obstac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 55 publications
(82 reference statements)
8
58
1
Order By: Relevance
“…In addition, some electrophysiological and anatomical studies have suggested that neurons in the primary motor cortex (M1) are involved in expressing muscle synergies in mammals (Drew et al 2008;Futami et al 1979;Gentner and Classen 2006;Li and Martin 2002;Shinoda et al 1976Shinoda et al , 1981Shinoda et al , 1986. We reason that the two views, derived from experiments with a lower vertebrate and mammals, respectively, could be reconciled in the sense that the "old" M1 (Rathelot and Strick 2009), sending descending fibers primarily to the spinal interneurons, generates movements by flexibly activating synergies expressed downstream, whereas the "new" M1 is involved in encoding the more diverse movements peculiar to higher primates and humans (Roh et al 2011a;Yakovenko et al 2011). Further studies may be needed to clarify how the synergy representation is organized in the cortex and downstream brain regions in the human.…”
Section: Neural Circuitries Involved In Expressing Muscle Synergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some electrophysiological and anatomical studies have suggested that neurons in the primary motor cortex (M1) are involved in expressing muscle synergies in mammals (Drew et al 2008;Futami et al 1979;Gentner and Classen 2006;Li and Martin 2002;Shinoda et al 1976Shinoda et al , 1981Shinoda et al , 1986. We reason that the two views, derived from experiments with a lower vertebrate and mammals, respectively, could be reconciled in the sense that the "old" M1 (Rathelot and Strick 2009), sending descending fibers primarily to the spinal interneurons, generates movements by flexibly activating synergies expressed downstream, whereas the "new" M1 is involved in encoding the more diverse movements peculiar to higher primates and humans (Roh et al 2011a;Yakovenko et al 2011). Further studies may be needed to clarify how the synergy representation is organized in the cortex and downstream brain regions in the human.…”
Section: Neural Circuitries Involved In Expressing Muscle Synergiesmentioning
confidence: 99%
“…An extensive set of experimental evidence has shown that a relatively small number of movement modules, or muscle synergies (assemblies of muscles with fixed relative levels of activation), may underlie posture and movement d'Avella et al 2003;Hart and Giszter 2004;Lee 1984;Macpherson et al 1986;Torres-Oviedo et al 2006;Tresch and Jarc 2009). Animal behaviors studied within the framework of muscle synergies include terrestrial and aquatic movements in the frog d'Avella et al 2003); postural responses, locomotion, and whole arm reaching in the cat (Krouchev et al 2006;Lockhart and Ting 2007;McKay and Ting 2008;Ting and Macpherson 2005;Torres-Oviedo et al 2006;Yakovenko et al 2011); and grasping and reaching in the monkey (Overduin et al 2008). Results of some of the animal studies suggest that neural circuits within the brain stem and/or spinal cord are involved in expressing muscle synergies (Giszter and Kargo 2000;Hart and Giszter 2010;Giszter 2000a, 2000b;Roh et al 2011a;Saltiel et al 1998Saltiel et al , 2001Saltiel et al , 2005Stein et al 1995;Tresch et al 1999).…”
mentioning
confidence: 99%
“…With respect to activations of specific groups of muscles, synergies have been proposed as building blocks of motor control (Grillner 1981;Ting and Macpherson 2004;Cheung et al 2005Cheung et al , 2009d'Avella et al 2006;Krouchev et al 2006;Yakovenko et al 2011;Overduin et al 2012;Berger et al 2013;Bizzi and Cheung 2013;Krouchev and Drew 2013). There is also evidence that encoding of muscle synergies already takes place in the spinal cord (Saltiel et al 2001;Stein 2008;Hart and Giszter 2010;Roh et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in extensor activity may contribute to facilitation of flexor activity in the contralateral leg of TTAmp volunteers (Ting et al, 1998) (see Figure 2, SND-TTAmp and Figure 3, SND-TTAmp knee and ankle moments). The compensatory activity adjustments of ampGAS and RF in the amputated leg and extensors of the sound contralateral leg in the amputees (Figures 6 and 7) could be discovered during voluntary modifications of commands to motoneuronal synergistic groups at the CPG pattern formation level (Markin et al, 2012; Yakovenko et al, 2011) and reinforced by skin afferents in the residuum interacting with the prosthetic socket during early stages of learning to pedal with the prosthetic leg. Extended cycling practice may strengthen the neural pathways in the brain (Cramer et al, 2011) and spinal cord (Wolpaw, 2012) that proved to be advantageous.…”
Section: Discussionmentioning
confidence: 99%